The Road to Mecca - Asad, Muhammad, 1900-1992 (London Max Reinhardt, 1954)
A South African pastor and a young teacher from Cape Town battle over the fate of an eccentric elderly widow.
Include Index
Keywords: Muslim converts -- Asad, Muhammad, 1900-1992